2020
DOI: 10.7717/peerj.9540
|View full text |Cite
|
Sign up to set email alerts
|

Predatory functional response and fitness parameters ofOrius strigicollisPoppius when fedBemisia tabaciandTrialeurodes vaporariorumas determined by age-stage, two-sex life table

Abstract: Background The polyphagous predatory bug O. strigicollis is an active predator used to control thrips and aphids. The whitefly species Bemisia tabaci and Trialeurodes vaporariorum are voracious pests of different economic agricultural crops and vegetables. Method In this study, the Holling disc equation and the age-stage, two-sex life table technique were used to investigate the functional response and biological traits of third instar nymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 96 publications
1
10
0
Order By: Relevance
“…Furthermore, the results revealed that feeding on B. tabaci had a significant effect on predatorsat different stages in the postoviposition and oviposition periods of the O. laevigatus female, whereas it was insignificant for the preoviposition period (Table 2). These data agreed with the findings of Rehman et al (2020), who discovered that O. strigicollis fed on B. tabaci or Trialeurodes vaporariorum under laboratory conditions (28°C ± 1°C temperature, 70% ± 5% RH, and a 16 L:8 D photoperiod at a light intensity of 1400-1725 lux. ).…”
Section: Duration Of O Laevigatus Male and Femalesupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the results revealed that feeding on B. tabaci had a significant effect on predatorsat different stages in the postoviposition and oviposition periods of the O. laevigatus female, whereas it was insignificant for the preoviposition period (Table 2). These data agreed with the findings of Rehman et al (2020), who discovered that O. strigicollis fed on B. tabaci or Trialeurodes vaporariorum under laboratory conditions (28°C ± 1°C temperature, 70% ± 5% RH, and a 16 L:8 D photoperiod at a light intensity of 1400-1725 lux. ).…”
Section: Duration Of O Laevigatus Male and Femalesupporting
confidence: 92%
“…For example, the shortest total nymph duration of the predator was 11.75 days when it fed on the whitefly adult, whereas the longest occurred when it fed on the first and second instars of nymphs (Table 1). Rehman et al (2020) similarly cited the duration of eggs and nymphs of O. strigicollis when the predator consumed B. tabaci at 25°C ± 1°C, 75% ± 5% RH, and a 16 L:8 D photoperiod.…”
Section: Duration Of O Laevigatus Immature Stagesmentioning
confidence: 99%
“…Similarly, Iqbal et al [ 51 ] used an age-stage, two-sex life table to investigate the impact that zinc oxide generated in the culture supernatant of B. thuringiensis had on the demographic characteristics of Musca domestica . Likewise, an age-stage, two-sex life table analysis was used to assess the predatory functional response and fitness characteristics of Orius strigicollis Poppius-fed Bemisia tabaci and Trialeurodes vaporariorum [ 52 ]. In the same way, ecotoxicological experiments were used to examine the sub-lethal effects of propargite on Amblyseius swirskii (Acari: Phytoseiidae) utilizing an age-stage, two-sex life table [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the arena consisted of small-scale setups such as plastic vials, which may have little resemblance to those experiments measured in natural conditions. In fact, this small experimental arena accelerated the search efficiency of the predatory bugs allowing them to repeatedly attack prey that initially escaped (Rehman et al 2020). Then these values are questionable to generate good representations of average natural predation levels and should be interpreted with care because of the poor chance for thrips to avoid predation (Kareiva 1990).…”
Section: Discussionmentioning
confidence: 99%